Pengaruh Organizational Justice Terhadap Outcome Measures - Ruth Moria .; Sunjoyo . (Jurnal Manajemen Maranatha, 2010)
This study examines the effects of organizational justice that consist procedural, distributive, interpersonal, and informational justice through outcome measures. Outcome measures consist of four dimensions which are outcome satisfaction, rule compliance, leader evaluation, and collective esteem. The questionnaires were distributed to 199 Maranatha Christian University's teachers of Economy and Phychology Faculty. A total of 67 teachers completed the questionnaires with a 56.3 per cent response rate, and only 64 data could be used. Normality, validity, reliability, and fitn ess model tests were done before the hypotheses testing. Five hypotheses are proposed in this study and structural equation modeling shows that all hypotheses are supported. The results indicate that organizational justice has direct effects on teacher's outcome measures.Keywords: organizational justice, outcome measures, structural equation modeling.